Online testing and assessment in the English as a foreign language context: Teachers' perspectives - Irem Gedil; Selami Aydin (Literacy Trek, 2023)
As online assessment is a rather new phenomenon, available research regarding it is limited, and most of the research in literature today examines the views of students regarding online assessment as they are one of the most important stakeholders of exams. On the other hand, although they are the basic users and practitioners of the system, studies on the views and perspectives of instructors on online assessment in the context of English as a foreign language (EFL) are limited in number. With these concerns in mind, this study aims to explore English instructors' perspectives of online assessment in tertiary educational institutions in Turkey with regard to their general views on online assessment, along with their views on affective factors, validity, reliability, security, practicality, and the impacts of online assessment on teaching and learning. In this descriptive study, the data were collected from 302 English instructors working at English preparatory schools in various universities in Turkey through a background questionnaire and the Student Perceptions of e-Assessment Questionnaire (SPEAQ). The results show that instructors' overall perspectives on online assessment are neutral.